THE ROLE OF BKM MANAGEMENT IN ENHANCING CONGREGATIONAL PARTICIPATION IN RELIGIOUS ACTIVITIES AT AL MA’SUM MOSQUE, MEDAN JOHOR DISTRICT - Muhammad Ridho Putra Aswan; Misrah Misrah (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2026)
This study aims to analyse the management of the Mosque Prosperity Board (BKM) with the objective of enhancing congregational participation in religious activities at the Al Ma’sum Mosque, situated in the Medan Johor District of Medan City. Specifically, this inquiry examines the operational application of core managerial functions namely planning, organizing, implementing, and controlling whilst identifying the salient facilitating and hindering factors encountered in the field. Methodologically, the study adopts a descriptive qualitative approach, positioning BKM administrators and congregants as primary informants. Data were collected comprehensively through in-depth interviews, direct observations, and document analysis. The empirical findings reveal that the BKM has formally and structurally instituted management functions through systematic religious program planning and an organised division of activities . Nevertheless, program execution remains suboptimal in fostering equitable congregational engagement, particularly failing to stimulate uniform participation among teenagers and the productive age demographic. Catalysts supporting BKM management include the solidarity of internal administrators, the adequacy of physical mosque facilities, the influential role of religious and community leaders, and robust social relationships amongst congregants. Conversely, institutional barriers include a scarcity of active human resources, fragile administrative and control mechanisms, a distinct lack of program innovation, and the suboptimal utilisation of digital information technology. This research provides valuable theoretical insights for Islamic da'wah management whilst offering practical stratagems to cultivate a more inclusive urban mosque ecosystem.